Preparation and Application of Mesoporous Nanotitania Photocatalysts Using Different Templates and pH Media - S. M. Abdel-Azim; A. K. Aboul-Gheit; S. M. Ahmed; D. S. El-Desouki; M. S. A. Abdel-Mottaleb (International Journal of Photoenergy)
Mesoporous nanotitania photocatalysts were prepared by sol-gel method in acidic or basic media. Three types of surfactants, namely, cetyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, and nonylphenol ethoxylate, were used as templating agents. The effects of surfactant type and pH on the morphology, particle size, surface area, pore-size distribution, UV-Vis absorbance, and TiO2 phase transformation were traced by SEM, TEM, BET, and XRD. In absence of surfactants, XRD revealed 54.5% anatase at pH 3-4 and 97.0% at pH 7–9. In presence of surfactant, phase transformation of anatase has been significantly inhibited such that anatase amounts to 82–100% in acidic media. In basic media, the brookite phase appeared in low concentrations (8–15%) while rutile totally disappeared. The photocatalytic performance of the synthesized catalysts was tested via naphthalene degradation, which exhibited high activity in visible irradiation (>400 nm). The data obtained indicate that the surface area and pore volume of the current catalysts are the most effective factors for photocatalytic performance. Nevertheless, at the low pH (acidic) range, the CTAB templated catalyst gave the highest surface area (86.7 cm3/g), which is mainly assigned to acquiring the highest photocatalytic degradation of naphthalene (97% after 4 h irradiation time).